2016
DOI: 10.1088/0953-2048/29/2/024008
|View full text |Cite
|
Sign up to set email alerts
|

Development of a brushless HTS exciter for a 10 kW HTS synchronous generator

Abstract: HTS synchronous generators, in which the rotor coils are wound from high-T c superconducting wire, are exciting attention due to their potential to deliver very high torque and power densities. However, injection of the large DC currents required by the HTS rotor coils presents a technical challenge. In this paper we discuss the development of a brushless HTS exciter which operates across the cryostat wall to inject a superconducting DC current into the rotor coil circuit. This approach fundamentally alters th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 44 publications
3
56
0
Order By: Relevance
“…In the present study with the flux pump, the same trend was observed and the non-uniform voltage profile observed across the HTS stator (see Figure 3) is similar to that of Bumby et al [16]. Based on the previous reported results [9], it is well established that the flux pump can be successfully used as an alternative to DC excitation for the field system in a generator.…”
Section: Performance Analysissupporting
confidence: 90%
“…In the present study with the flux pump, the same trend was observed and the non-uniform voltage profile observed across the HTS stator (see Figure 3) is similar to that of Bumby et al [16]. Based on the previous reported results [9], it is well established that the flux pump can be successfully used as an alternative to DC excitation for the field system in a generator.…”
Section: Performance Analysissupporting
confidence: 90%
“…REBCO coated conductors have also been demonstrated in a magnet with an overall 42.5 T field generated by a 11.3 T REBCO insert coil in a 31.2 T background field 5 , a 26 T superconducting magnet 6 , and the concept design of a 100 T magnet 7 . Moreover, prototype coils for rotation machinery applications 8 , superconducting magnetic energy storage 9 , magnetic resonance imaging and nuclear magnetic resonance 10–12 , and high energy physics 13, 14 are being extensively investigated. A critical need for high field magnet R&D is the substantially increased performance and reduced cost, and aggressively pursuing the development of superconducting magnets 15 .…”
Section: Introductionmentioning
confidence: 99%
“…HTS field windings in rotating machines experience an applied ripple field whilst carrying a DC current. The resulting dynamic resistance leads to heat dissipation which may impose a substantial heat load on the cryogenic system [6][7][8]. Dynamic resistance is also critical to the design and operation of HTS flux pumps, as it sets a limit to the maximum achievable current which such devices can deliver [9][10][11][12][13].…”
mentioning
confidence: 99%